What are NLRP3-ASC specks? an experimental progress of 22 years of inflammasome research - Nagar, Abhinit; Bharadwaj, Ravi; Shaikh, Mohammad Omar Faruk; Roy, Abhishek (Frontiers in Immunology, 2023)
Speck assembly is the hallmark of NLRP3 inflammasome activation. The 1µm structure comprising of NLRP3 and ASC is the first observable phenotype of NLRP3 activation.While the common consensus is that the specks are the site of inflammasome activity, no direct experimental evidence exists to support this notion. In these 22 years, since the inflammasome discovery, several research studies have been published which directly or indirectly support or refute the idea of speck being the inflammasome. This review compiles the data from two decades of research to answer a long-standing question:"What are NLRP3-ASC specks?"